Integrasi Agama dan Sains Dalam Perspektif Abdussalam Solutif-Sintesisnya Terhadap Problema Pendidikan Islam - Muhartini Muhartini; Amril Amril (SOKO GURU: Jurnal Ilmu Pendidikan, 2023)
The integration of religion and science is a very good discourse, because it seeks to connect religion and science, which has been considered something that cannot be sought relations. Religion and science are not separated, but a relationship must be sought between the two. Religion and science are actually two things that have the same entity. The proof, many things researched by science, are in line with what religion confirms. In fact, long before the existence of such research, religion had already explained it in the scriptures. Therefore, religion and science are two things that are interconnected with each other. Religion needs science, and science also needs religion. Abdussalam grew up in two different and opposite lives. On the one hand, he became a very religiously devout man and found justification in the Qur'an that always inspired the rationale of his scientific work. In relation to the integration of religion and science, what is needed for Islamic education today is an education system called Interdiscipline Sciences in Islam. With the new education system where the curriculum taught is a complete union between the value of revelation and science. So it is hoped that alumni of Islamic educational institutions will be able to describe the methods of science and religion in the form of ways of thinking and behavior (akhlaq) in an integrated and comprehensive (holistic) manner in society so that in the future a better community order will be created.